THE CONSTRUCTION OF HADITH ADDRESSING GENETIC ENGINEERING OF HUMANS - Tangngareng, Tasmim; Abdullah, Irwan; Rahman, Rahman; Sawaluddin, Sawaluddin (Islam Futura, 2023)
This paper explores positions of hadith and ethics in discussing the genetic engineering of humans by departing from the following questions: a) how do hadith contribute to constructing various aspects of human genetics? b) how did the social context around Prophet Muhammad affect the construction of the hadith? c) how do hadith addressing human genetics relate to scientific development? This paper reveals that the ethics and process of genetic engineering are prescribed in the hadith, illuminating the contextual debates of its time. Issues of genetics that arise in the discourse of human existence, particularly regarding sex and skin color, show a contestation of values related to the position of genetic factors as undeniable. Scientific development provides answers to the increasingly complex and contestatory discourse on genetics and necessitates a paradigm shift in the Muslim community, which often places hadith as a believed and practiced textual truth